Leadership: The Multiplier Effect - Andy Cope (John Murray Learning, 2018)
The leader's job is to squeeze more from less, but most leaders feel they can't possibly work any harder and are sick to death with being told to work smarter. So where next? The answer is to use the multiplier effect to transform your leadership style. Good emotions spread far wider than we realise. A good leader who is inspired and inspiring will spread good feelings throughout his team. But it won't stop there. They in turn will pass good feelings on to their colleagues, clients and customers, who will pass on positive emotions in turn. The multiplier effect is the organic set of positive emotions which flow out in ripples from good leadership. This book shows how to lead well by being the secret ingredient in your team's everyday happiness - just by making them feel good and empowering them to pass it on. Leadership: The Multiplier Effect is crammed with the latest thinking on leadership, strengths, positive psychology, purpose, employee engagement, coaching, emotional intelligence and 'life', supplemented with anecdotes, pithy quotes and asides that help bring the content to life. And to save you time, the book's central message is this: Your job as a leader is NOT to inspire people. Your job as a leader is to BE INSPIRED.
Keywords: Leadeship